Development of instagram social media as a non-toxic application with positive and interactive information - Magdalena Palang Lewoleba; Maria Vianey Agustiningsih Dyah Kurniasa; Hillary Wixie Reandsi; Gabriela Basilisa (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2022)
Instagram is one of the social media that is widely used by people in Indonesia from various backgrounds and various age groups. Various information can be obtained easily from social media, including Instagram. Instagram users can share information with each other in the form of photos and videos, the information conveyed is of various types, ranging from news, to just updating the personal lives of Instagram users. The use of Instagram can have both positive and negative impacts. This research was conducted to determine the views of Instagram users and the desired content of Instagram users as a social media that they often use and to develop the use of Instagram as a technological medium that can be used to spread positive information. The type of research used is Research and Development (R&D), the population in this study is Instagram users with several age groups. The data obtained were then analyzed using several theories from various references studied by researchers. The conclusion in this study shows that respondents feel that the content that we present on Instagram is useful and interesting content.